2002
DOI: 10.1017/s1464793101005814
|View full text |Cite
|
Sign up to set email alerts
|

Sexual segregation in ungulates: a comparative test of three hypotheses

Abstract: In most social ungulate species, males are larger than females and the sexes live in separate groups outside the breeding season. It is important for our understanding of the evolution of sociality to find out why sexual segregation is so widespread not only in ungulates but also in other mammals. Sexual body size dimorphism was proposed as a central factor in the evolution of sexual segregation in ungulates. We tested three hypotheses put forward to explain sexual segregation : the predation-risk, the forage-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
309
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(329 citation statements)
references
References 78 publications
17
309
2
1
Order By: Relevance
“…(d ) Lack of evidence for the 'forage-selection' hypothesis We found no support for the 'forage-selection' hypothesis in accordance with other recent results (Conradt 1999;Conradt et al 1999), although red deer are one of the most dimorphic ungulate species (more dimorphic than the 20% threshold needed for sexual segregation to occur; Ruckstuhl & Neuhaus 2002) and several empirical studies provide evidence for males having higher energy needs than females. However, the Jarman-Bell principle was coined at the interspecific level to explain variations in energy requirements and differences in diet selection between the African elephant (Loxodonta africana) and dik-dik (Madoqua kirki ) and more recently between the cow (Bos taurus) (750 kg) and Thomson's gazelle (Gazella thomsoni ) (20 kg) (Wilmshurst et al 2000).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…(d ) Lack of evidence for the 'forage-selection' hypothesis We found no support for the 'forage-selection' hypothesis in accordance with other recent results (Conradt 1999;Conradt et al 1999), although red deer are one of the most dimorphic ungulate species (more dimorphic than the 20% threshold needed for sexual segregation to occur; Ruckstuhl & Neuhaus 2002) and several empirical studies provide evidence for males having higher energy needs than females. However, the Jarman-Bell principle was coined at the interspecific level to explain variations in energy requirements and differences in diet selection between the African elephant (Loxodonta africana) and dik-dik (Madoqua kirki ) and more recently between the cow (Bos taurus) (750 kg) and Thomson's gazelle (Gazella thomsoni ) (20 kg) (Wilmshurst et al 2000).…”
Section: Discussionsupporting
confidence: 62%
“…Energetic needs are highest when the females lactate because the production of milk is extremely costly (Sadleir 1969;Loudon 1985;Robbins 1993). Lactating females can therefore have a different activity budget from other females (Ruckstuhl & Neuhaus 2002). Females with calves were more socially segregated from males than were females without calves.…”
Section: Discussionmentioning
confidence: 99%
“…In many situations conflicts may exist between the preferences of different group members (Conradt 1998;Ruckstuhl 1998;Ruckstuhl & Neuhaus 2000;Ruckstuhl & Neuhaus 2002;Couzin et al 2005). If these conflicts cannot be resolved and no consensus can be reached then the group will split and individuals will forego the benefits associated with being part of a large group (Krause & Ruxton 2002).…”
mentioning
confidence: 99%
“…It is possible that variation in mass was insufficient to affect associations. For example, Ruckstuhl and Neuhaus (2002) showed that there was a threshold that maleefemale body mass differences should exceed for sexes to segregate. Alternatively, female differences in body mass may be heritable as in many other ungulate species (Pelletier, Reale, Garant, Coltman, & Festa-Bianchet, 2007;Wilson & Reale, 2006), and associations between mothers and daughters may hide potential association patterns of females with different body masses.…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive status could also influence female associations and group formation. In ungulates, lactating females forage longer than nonlactating females (Hamel & CĂŽte, 2008;Ruckstuhl & Neuhaus, 2002). Therefore, segregation of females of different reproductive status may result from a lack of synchronization generated by different time budgets.…”
mentioning
confidence: 99%